Epigenomic profiling of DNA methylation for hepatocellular carcinoma diagnosis and prognosis prediction. Issue 10 (20th June 2019) - Zhang, Cheng; Ge, Shuang; Wang, Jun; Jing, Xiaotong; Li, Hailing; Mei, Shuyu; Zhang, Juan; Liang, Ke; Xu, Hui; Zhang, Xiaoying; Zhang, Cuijuan
Abstract: Background and Aim: DNA hypermethylation has emerged as a novel molecular biomarker for the diagnosis and prognosis prediction of many cancers. We aimed to identify clinically useful biomarkers regulated by DNA methylation in hepatocellular carcinoma (HCC). Methods: Genome‐wide methylation analysis in HCCs and paired noncancerous tissues was performed using an Illumina Infinium HumanMethylation 450K BeadChip array. Methylation‐specific polymerase chain reaction and pyrosequencing were used to validate the methylation status of selected genes in 100 paired HCCs and noncancerous samples. Results: A total of 97 027 (20.0%) out of 485 577 CpG sites significantly were differed between HCC and noncancerous tissues. Among all the significant CpG sites, 48.8% are hypermethylated and 51.2% are hypomethylated in HCCs. Multiple signaling pathways (AMP‐activated protein kinase, estrogen, and adipocytokine) involved in gene methylation were identified in HCC. FES was selected for further analysis based on its high level of methylation confirmed by polymerase chain reaction and pyrosequencing. The result showed that FES hypermethylation was correlated with tumor size (0.001), serum alpha fetoprotein (0.023), and tumor differentiation (0.006). FES protein was significantly downregulated in 51/100 (51%) HCCs, and 94.12% (48/51) of them were due to promoter hypermethylation. Both FES hypermethylation and protein downregulation were associated with the progression‐free survival and overall survival of HCC patients. Overexpressed and knockdown of FES confirmed its inhibitory effect on the proliferation and migration of HCC cells. Conclusions: We identified many new differentially methylated CpGs in HCCs and demonstrate that FES functions as a tumor suppressor gene in HCC and its methylation status could be used as an indicator for prognosis of HCC.